Prácticas desarrolladas por los trabajadores con predominio del trabajo manual: caso de estiba de productos pesqueros - Carolina Ullilen-Marcilla; Romel Ullilen-Marcilla (Universidade do Porto, 2018)
In the port terminals of Peru, the placement of fishery products such as frozen fish within refrigerated containers is done manually with the help of gaff hooks. The workers are organized into groups according to their experiences and knowledge in order to meet the production goals, following the quality and safety standards indicated by the organization. The introduction of technologies in the process of cargo stowage did not meet the expected results on reducing the long-term physical effects on operational personnel, who are the ones with the knowledge for the processes, which represents a disregard of the experience and loss of money in technology that is wrongly used by the workers. The challenge of this ergonomic intervention is to analyze the process of cargo stowage of frozen fish under a systematic approach to understand the ways and factors of this job, while getting the workers involved.